Wearables as Context for Guiard-abiding Bimanual Touch - Pahud, Michel; Hinckley, Ken; Buxton, Bill (UIST '16 Proceedings of the 29th Annual Symposium on User Interface Software and Technology, 2016)
We explore the contextual details afforded by wearable devices to support multi-user, direct-touch interaction on electronic whiteboards in a way that—unlike previous work—can be fully consistent with natural bimanual-asymmetric interaction as set forth by Guiard. Our work offers the following key observation. While Guiard’s framework has been widely applied in HCI, for bimanual interfaces where each hand interacts via direct touch, subtle limitations of multi-touch technologies—as well as limitations in conception and design—mean that the resulting interfaces often cannot fully adhere to Guiard’s principles even if they want to. The interactions are fundamentally ambiguous because the system does not know which hand, left or right, contributes each touch. But by integrating additional context from wearable devices, our system can identify which user is touching, as well as distinguish what hand they use to do so. This enables our prototypes to respect lateral preference—the assignment of natural roles to each hand as advocated by Guiard—in a way that has not been articulated before.